2013
DOI: 10.1097/pec.0b013e31828a3663
|View full text |Cite
|
Sign up to set email alerts
|

Development of Pyloric Stenosis After a 4-Day Course of Oral Erythromycin

Abstract: Early exposure to oral erythromycin in young infants, particularly in the first 2 weeks of life, has previously been associated with the development of hypertrophic pyloric stenosis. We report a case of an infant who received an abbreviated 4-day course of oral erythromycin for suspected Chlamydia conjunctivitis at 5 days of life then underwent pyloromyotomy for pyloric stenosis less than 2 weeks later. Health care providers should use erythromycin judiciously in neonates because only a few days of exposure to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Among the three most widely prescribed macrolides, azithromycin is the only recommended antimicrobial for neonates (Ͻ1 month old) (278). Erythromycin has been linked with infantile hypertrophic pyloric stenosis (IHPS) in neonates, including those indirectly receiving erythromycin through breast milk (278,344,345). In one cohort study, infants receiving erythromycin prophylaxis were found to have greater risk of IHPS (7/157 among those exposed versus 0/125 among those with no erythromycin exposure) (278).…”
Section: Postexposure Prophylaxis and Therapeuticsmentioning
confidence: 99%
“…Among the three most widely prescribed macrolides, azithromycin is the only recommended antimicrobial for neonates (Ͻ1 month old) (278). Erythromycin has been linked with infantile hypertrophic pyloric stenosis (IHPS) in neonates, including those indirectly receiving erythromycin through breast milk (278,344,345). In one cohort study, infants receiving erythromycin prophylaxis were found to have greater risk of IHPS (7/157 among those exposed versus 0/125 among those with no erythromycin exposure) (278).…”
Section: Postexposure Prophylaxis and Therapeuticsmentioning
confidence: 99%
“…The major concern associated with the use of macrolides in nursing mothers is related to numerous cases of pyloric stenosis in children treated with this antibiotic [69,70,71,72]. However, studies conducted in nursing mothers treated with erythromycin are conflicting, with some authors reporting the onset of pyloric stenosis [73,74] and other authors reporting a relationship between antibiotic use by the mother and the development of pyloric stenosis [38,71,75].…”
Section: Main Antibiotics In Clinical Usementioning
confidence: 93%
“…The exact etiology is unknown however several studies have suggested a correlation with: genetic factors, 10 maternal smoking during pregnancy, preterm birth, reduced weight for gestational age, cesarean section, 11 young maternal age 12 and exposure to erythromycin during the neonatal period, in particular during the first two weeks after birth. [13][14][15] The HPS presents a correlation with the family history: 17% of risk in one member of the family, 3% in two or more members. 16 In particular, if the father was affected by the condition, the risk of a child with the same condition is equal to 7%; if the mother was the one affected, the risk increases 4 times.…”
Section: Definitionmentioning
confidence: 99%